THE EFFECT OF EMPLOYEE ENGAGEMENT AND BURNOUT ON EMPLOYEE TURNOVER INTENTION AT DINASTY MUSIC EQUIPMENT SEMARANG - Mochammad Marzha Adyllah H; Kiki Sudiana (RADJA PUBLIKA, 2026)
The increasingly tight competition in the event organizer industry requires companies to have competent human resources capable of providing quality services. The importance of human resources in supporting the success of event organizer companies that are oriented towards service quality and customer satisfaction makes employee management a very strategic aspect. Companies need employees who are highly engaged in their work and are able to work optimally without experiencing excessive work fatigue. This study aims to analyze the effect of employee engagement on turnover intention. To analyze the effect of burnout on employee turnover intention. This type of research uses a causal explanatory method with a quantitative approach. The population of this study was employees of Dynasty Music Equipment Semarang, with a total of 55 respondents. The data collection technique in this study was carried out by distributing questionnaires with a 5-point Likert scale. The analysis tool used in this study was Smart PLS 4.0. The results of the study showed that: (1) There is no effect of employee engagement variables on Turnover Intention in Dynasty Music Equipment Semarang employees with ap value of 0.059>0.05. (2) The p-value of 0.059>0.05 indicates that burnout influences turnover intention among employees at Dynasty Music Equipment Semarang, with a p-value of 0.000<0.05. The research findings indicate that employee engagement does not influence employee turnover intention at Dynasty Music Equipment Semarang. Conversely, burnout has a positive effect on turnover intention, meaning that the higher the level of burnout experienced by employees, the higher their desire to leave the company. Therefore, companies need to prioritize burnout prevention and management efforts to reduce employee turnover intention.